Impact of International Organizations on Education Development in Federal Capital Territory, Abuja: A Case of FCT Basic Education - Akuh, Esther Amina (International Journal of Applied Educational Research (IJAER), 2024)
This article examined the impact of international organizations on educational development in the Federal Capital Territory of Abuja, using FCT Basic Education as a case study. The study used a correlational type descriptive research design. The sample for this study consisted of 63 principals and 260 teachers. As of December 2023, the population included 99 school principals and 8,321 teachers in the district councils surveyed. The multi-stage procedure was used for the investigation. Using random sampling technique, three of the six area councils (Abaji, Gwagwalada and Bwari area councils in FCT) in the area were selected. In this study, the International Questionnaire (IQ) was used to collect information from both school principals and teachers. Three lecturers from the Department of Educational Management, University of Abuja and two specialists in educational research, measurement and evaluation determined the face validity and content of the instruments. The study used the test-retest method for reliability. The IQ yielded a reliability coefficient of 0.65 and 0.75 for IQ, respectively. Inferential and descriptive statistics were used to analyze the data for the study. Mean and standard deviation were used to answer the research questions, while the hypotheses were tested using simple regression analysis for the main hypothesis and Pearson product moment correlation statistics (PPMC) for the operational hypotheses. The hypotheses were confirmed at 05 levels of significance. The paper revealed that international organizations in the Federal Capital Territory of Abuja have contributed to the development of education (basic education) in FCT and it was also found that there is a significant relationship between international organizations and the development of education (basic education) in FCT, Abuja, Nigeria. Based on the findings of this study, the paper recommends that the Nigerian government should establish more diplomatic relations with more developed countries to attract more aid for the education system. Governments should establish a commission responsible for coordinating international organizations based in Nigeria to better manage their donations for the development of education.